O impacto da interatividade mobile na utilização de aplicativos de delivery de comida com usuários da base da pirâmide - Cruz, Diogo Leite da (2023)
Technological advances have brought benefits to the world's population, especially those who belong to the Base of the Pyramid (BoP), considered as low-income people. Among the benefits, the proliferation of food delivery apps that had its growth driven by the COVID-19 pandemic. These apps allow convenience and practicality in the purchase and delivery of meals. However, it is assumed that the continuity of use of these applications is due to technological resources, among them, mobile interactivity, which, in turn, can positively impact ease of use, satisfaction, repurchase intention, word of mouth recommendation and brand loyalty. To get a better understanding of how these features improve users' propensity to use them continuously, this study aimed to verify the impact of mobile interactivity on the use of these food delivery apps by users at the bottom of the pyramid. Consequently, measuring whether mobile interactivity positively impacts ease of use, satisfaction, repurchase intention, word-of-mouth recommendation and brand loyalty. To achieve the objective, a collection of data obtained through a survey was carried out with 278 users of BoP food delivery applications in Brazil. Data were analyzed using Partial Least Squares Structural Equation Modeling (with SmartPLS software). As the main finding, the second-order construct, mobile interactivity, remained valid. Also, the mediating effect of mobile ease between mobile interactivity and satisfaction, the mediating effect of satisfaction between mobile interactivity and repurchase intention, word of mouth recommendation and brand loyalty. Thus, the results corroborate the importance and impacts of mobile interactivity in the use of food delivery applications with BoP users. This study brings theoretical, practical and social contributions. In this way, it is expected to contribute to the practice, indicating the relevance of investments in improvements to make the application more interactive and, therefore, increase repurchase, recommendation and brand loyalty. There is a desire to contribute socially, with awareness regarding the use of food delivery applications with BoP users.